THE EFFECTIVENESS OF MAKE A MATCH METHOD IN IMPROVING STUDENTS’ WRITING SKILLS - Asni, Yulie; Tsuraya, Annisa Shofa; Muthi'ah, Muthi'ah; Abubakar, Multazam (English Language, Linguistics, and Culture International Journal, 2021)
This research aimed to explain how the use of “Make a Match Method” was able to improve the students’ writing descriptive text view from content aspect and explain how the use of “Make a Match Method” was able to improve the students’ writing descriptive text view from grammar aspect. The researcher used a pre-experimental design with one group pre-test and post-test design. The population was the seventh-grade students of one of junior high schools in Gowa which consisted of one class. The sample was taken by total sampling technique and the total number of samples was 28 students. It employed six meetings which writing test as the instrument. The research findings indicated that the use of “Make a Match Method” could improve the students’ writing skill view from content aspect and grammar aspect. It was proven by the students’ mean score in post-test (75.36) improved 25.6% from the pre-test mean score (60) with t-test 25.545 and t-table 2.052 where (25.545 > 2.052). It was improved because the t-test was higher than t-table. It meant that there was significant difference of the students’ writing descriptive text before and after being taught through Make a Match Method.